West of Kabul, East of New York : An Afghan American Story - Ansary, Tamim 1948- (New York Farrar, Straus and Giroux, 2002)
The day after the World Trade Center was destroyed, Tamim Ansary sent an anguished e-mail to twenty friends discussing the attack from his perspective as an Afghan American. The message reached millions. Born to an Afghan father and American mother, Ansary grew up in the intimate world of Afghan family life. When he emigrated to San Francisco, he believed he'd left Afghan culture behind forever. But at the height of the Iranian Revolution, he took a harrowing journey through the Islamic world to rediscover his roots. In the years that followed, he struggled to unite his divided self and to find a place in his imagination where his Afghan and American identities might meet.
Include Emails
Keywords: Afghan Americans -- Islamic Civilization--Western Influences -- California--San Francisco -- Islamic Civilization -- Social Conditions